Prisoner of lies : Jack Downey's Cold War - Werth, Barry (Simon & Schuster, 2024)
John (Jack) Downey, Jr., was a new Yale graduate in the post-World War II years who, like other Yale grads, was recruited by the young CIA. He joined the Agency and was sent to Japan in 1952, during the Korean War. In a violation of protocol, he took part in an air drop that failed and was captured over China. His sources on the ground had been compromised, and his identity was known. Although he first tried to deny who he was, he eventually admitted the truth. But government policy forbade ever acknowledging the identity of spies, no matter the consequences. Washington invented a fictitious cover story and stood by it through four Administrations. As a result, Downey was imprisoned during the decades that Red China, as it was called, was considered by the US to be a hostile nation, until 1973, when the US finally recognized the mainland Chinese government. He had spent twenty-one years in captivity. Downey would go on to become a lawyer and an esteemed judge in Connecticut, his home state. Prisoners of Lies is based in part on a prison memoir that Downey wrote several years after his release. Barry Werth fluently weaves excerpts from the memoir with the Cold War events that determined Downey's fate. Like a le Carré novel, this is a harrowing, chilling story of one man whose life is at the mercy of larger forces outside of his control; in Downey's case as a pawn of the Cold War, and more specifically the Oval Office and the State Department. His freedom came only when US foreign policy dramatically changed. Above all, Prisoner of Lies is an inspiring story of remarkable fortitude and resilience.